2016
DOI: 10.3389/fnhum.2016.00490
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Brain Regional Homogeneity and Functional Connectivity in Middle-Aged T2DM Patients: A Resting-State Functional MRI Study

Abstract: Type 2 diabetes mellitus (T2DM) has been associated with cognitive impairment. However, its neurological mechanism remains elusive. Combining regional homogeneity (ReHo) and functional connectivity (FC) analyses, the present study aimed to investigate brain functional alterations in middle-aged T2DM patients, which could provide complementary information for the neural substrates underlying T2DM-associated brain dysfunction. Twenty-five T2DM patients and 25 healthy controls were involved in neuropsychological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 46 publications
1
39
1
Order By: Relevance
“…Additionally, the patients with lower HbA 1c levels obtained higher scores on the DST forwards. The results were similar to those of several previous studies, which indicated that T2DM patients with elevated glycemic parameters exhibited decreased/inverted brain functional activity and poor cognitive performance (Xia et al, 2013 ; Chen et al, 2014 ; Liu D. et al, 2016 ; Yang et al, 2016 ). However, the findings of this study did not provide sufficient information about the relationships between the altered brain function and cognitive performance.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Additionally, the patients with lower HbA 1c levels obtained higher scores on the DST forwards. The results were similar to those of several previous studies, which indicated that T2DM patients with elevated glycemic parameters exhibited decreased/inverted brain functional activity and poor cognitive performance (Xia et al, 2013 ; Chen et al, 2014 ; Liu D. et al, 2016 ; Yang et al, 2016 ). However, the findings of this study did not provide sufficient information about the relationships between the altered brain function and cognitive performance.…”
Section: Discussionsupporting
confidence: 91%
“…The brain regions where identified hubs are located have been reported to be abnormal in previous studies using other neuroimaging metrics in T2DM patients, which suggests that these brain regions are susceptible to T2DM. The ACG is usually identified as the disturbed brain region across experiments and appeared with increased amplitude of low-frequency fluctuation, regional homogeneity (Cui et al, 2014 ; Liu D. et al, 2016 ), and cerebral blood flow (Cui et al, 2017 ). The aforementioned hyperactivity of ACG has usually been regarded as a means to compensate for the cognitive loss and maintain normal cognition (He et al, 2015 ; Liu D. et al, 2016 ; Cui et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Besides the above discussion, ReHo value abnormalities in the FG were also seen in depression disorder (Liu et al. ; Shen et al. ).…”
Section: Discussionmentioning
confidence: 86%
“…In addition, the ReHo measure is usually used to characterize spontaneous brain activity at a limited anatomical distance, while the FC is applied to characterize the correlation of the functional patterns of blood oxygen level-dependent signals in between spatially distant brain areas at a network level. Thus, the two analyses, ReHo and FC, are considered to be mutually complementary for detecting both local and remote brain activity synchronization (Cui et al, 2016 ), and have conjunctively applied in other diseases (Liu et al, 2016 ). However, for functional networks in hepatitis B virus-related cirrhosis (HBV-RC) patients with or without MHE, abnormalities of regional and inter-regional function interaction patterns have not been well characterized either.…”
Section: Introductionmentioning
confidence: 99%
“…This study aimed to explore the local coherence of intrinsic brain activity and inter-regional connectivity features in patients with and without MHE by using ReHo and ROI-based FC analysis. Based on previous findings that there are abnormalities in both local brain activity and FC in one disease simultaneously (Liu et al, 2016 ; Lv et al, 2017 ), we hypothesized that: (1) regional disturbances of ReHo at both cortical and subcortical levels could be detected in HBV-RC patients with or without MHE; (2) the MHE/NMHE patients showed alterations in intrinsic functional connections between different ROI regions pairs; and (3) changes of ReHo and FC in specific functional networks might be correlated with the disease duration or neuropsychological performances measured by the PHES tests.…”
Section: Introductionmentioning
confidence: 99%